A Note on Padé Approximants Pairs as Limits of Algebraic Polynomials Pairs of Weighted Best Approximation in Orlicz Spaces (Analysis in Theory and Applications, 2017)
In this short note, we show the behavior in Orlicz spaces of best approximationsby algebraic polynomials pairs on union of neighborhoods, when the measure ofthem tends to zero.